Customers’ Trust in E-payment: The Influence of Security and Privacy - Poudel, Omkar; Acharya, Pradeep; Simkhada, Daya (BMC Journal of Scientific Research, 2023)
Security and Privacy are the key factors in the digital payment platform. With the advancement of the technology the use of the digital payment platform has largely increased. How people perceive the security and privacy factors are important determining factors for using and not using the digital payment platform. Perceived ease of use and Perceived Usefulness also have a defining impact on individual’s intention to use the digital payment platform. This paper tends to study the impact of security and privacy perceptions on customers trust among digital payment users and also the impact of perceived usefulness and perceived use of use on customers intention to use digital payment. For the purpose of the study 327 samples on the basis of past research conducted were collected and after the reliability and validity test, path analysis was employed to test hypothesis. The result suggests that security and privacy perceptions have significant impact on customers trust and also the trust do have significant positive impact on customer’s intention to use. On the other hand perceived ease of use and perceived usefulness also have significant impact on customers intention to digital payment technology.